2019
DOI: 10.1016/j.energy.2018.12.199
|View full text |Cite
|
Sign up to set email alerts
|

Are renewables affecting income distribution and increasing the risk of household poverty?

Abstract: The worldwide electricity mix has become diversified, mainly through the exploitation of endogenous and green resources. However, doubt has been cast on the much-vaunted advantages of renewables due to some of their characteristics, such as availability, security and affordability. In fact, growth in the installed capacity of renewable energy has increased electricity prices, which raises the question of how households have withstood the cost of energy transition. The main aim of this study is to empirically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…barriers that are hampering the penetration of renewables in households. The scholars have shown in their studies that renewable energy subsidies had a positive effect on the use of renewable energy sources and the feed-in tariffs are successful in the promotion of the adoption of solar energy [43][44][45][46]. Lekavičius et al [47] claim that although funding is energy efficient, it mostly favors households with higher incomes because vulnerable households have limited investment opportunities.…”
Section: Policies To Overcome Barriers Of Renewable Energy Technologi...mentioning
confidence: 99%
“…barriers that are hampering the penetration of renewables in households. The scholars have shown in their studies that renewable energy subsidies had a positive effect on the use of renewable energy sources and the feed-in tariffs are successful in the promotion of the adoption of solar energy [43][44][45][46]. Lekavičius et al [47] claim that although funding is energy efficient, it mostly favors households with higher incomes because vulnerable households have limited investment opportunities.…”
Section: Policies To Overcome Barriers Of Renewable Energy Technologi...mentioning
confidence: 99%
“…However, many empirical studies (Bedir et al, 2013;, which included household size as a continuous variable in their prediction models, showed that there is a positive relationship between this variable and the amount of energy consumed in the dwelling. Other factors such as age of household reference person (HRP), income, presence of children, level of education, and tenure mode, were also found to influence the variation in energy consumption (Pereira et al, 2019). However, their significance and magnitude are still inconsistent in the literature.…”
Section: The Effect Of Psychological Factorsmentioning
confidence: 99%
“…The impact of Distributed Generation (DG) on low-income consumers and its impact on energy poverty has been studied in various ways: there are studies about the effective way to overcome domestic energy poverty in developing regions using solar home systems [24], an Indian case also about solar home systems to reduce energy poverty [25] and there is a study questioning if the renewable 's are affecting income distribution and increasing the risk of household poverty [26]. In Brazil there is an aggravation scenario in this situation, when evaluating the history of average electric energy tariffs.…”
Section: How Distributed Generation (Dg) Can Intensify This Differencementioning
confidence: 99%